2020
DOI: 10.1016/j.radcr.2020.08.015
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pneumonia identified by CT of the abdomen: A report of three emergency patients presenting with abdominal pain

Abstract: Patients with COVID-19 infection may present to the Emergency Department (ED) with gastrointestinal complaints and no respiratory symptoms. We are presenting 3 patients who came to the ED with abdominal pain; and the computed tomography [CT] of the abdomen showed findings suggestive of COVID-19 pneumonia. A 65-year-old male patient presented with symptoms of urinary tract infection and left renal angle tenderness. A 42-year-old male patient presented with right flank pain postextracorporeal shock wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Multiple studies have recently reported the abdominopelvic findings on CT scans of the abdomen and pelvis in COVID-19 patients with abdominal symptoms [ 9 18 ]. However, a significant number of COVID-19 patients undergo only a chest CT.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have recently reported the abdominopelvic findings on CT scans of the abdomen and pelvis in COVID-19 patients with abdominal symptoms [ 9 18 ]. However, a significant number of COVID-19 patients undergo only a chest CT.…”
Section: Introductionmentioning
confidence: 99%
“…None of these patients had pulmonary CT. Abnormal imaging findings were seen on the pulmonary component of abdominal CT in two of these patients (20). Similarly, other studies examining this issue consisted of case series (21)(22)(23)(24). Moreover, in their study, Barkmeier et al stated that there were 42 patients with COVID-19 have abdominal CT that visualized lung bases.…”
Section: Discussionmentioning
confidence: 87%
“…Details of these studies are shown in Table 1 and online supplementary Table 1 (for all online suppl. material, see www.karger.com/doi/10.1159/000518473 ) [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 …”
Section: Resultsmentioning
confidence: 99%
“…Another study by Tirumani et al [ 10 ] showed that among 59 patients having normal imaging findings, 18 (31%) patients were having abdominal symptoms. Additionally, many case series have shown the importance of lung base findings in detecting COVID-19 in otherwise normal abdominal scans [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 30 ].…”
Section: Resultsmentioning
confidence: 99%